Plasma-derived exosome characterization reveals a distinct microRNA signature in long duration Type 1 diabetes - Marta Garcia-Contreras (Nature Portfolio, 2017)
Abstract Type 1 diabetes mellitus (T1DM) results from an autoimmune attack against the insulin-producing ß cells which leads to chronic hyperglycemia. Exosomes are lipid vesicles derived from cellular multivesicular bodies that are enriched in specific miRNAs, potentially providing a disease-specific diagnostic signature. To assess the value of exosome miRNAs as biomarkers for T1DM, miRNA expression in plasma-derived exosomes was measured. Nanoparticle tracking analysis and transmission electron microscopy confirmed the presence of plasma-derived exosomes (EXOs) isolated by differential centrifugation. Total RNA extracted from plasma-derived EXOs of 12 T1DM and 12 control subjects was hybridized onto Nanostring human v2 miRNA microarray array and expression data were analyzed on nSolver analysis software. We found 7 different miRNAs (1 up-regulated and 6 down-regulated), that were differentially expressed in T1DM. The selected candidate miRNAs were validated by qRT-PCR analysis of cohorts of 24 T1DM and 24 control subjects. Most of the deregulated miRNAs are involved in progression of T1DM. These findings highlight the potential of EXOs miRNA profiling in the diagnosis as well as new insights into the molecular mechanisms involved in T1DM.